Multifunctional Thioredoxin-Like Protein from the Gastrointestinal Parasitic Nematodes Strongyloides ratti and Trichuris suis Affects Mucosal Homeostasis - Dana Ditgen; Emmanuela M. Anandarajah; Jan Hansmann; Dominic Winter; Guido Schramm; Klaus D. Erttmann; Eva Liebau; Norbert W. Brattig (Journal of Parasitology Research)
The cellular redox state is important for the regulation of multiple functions and is essential for the maintenance of cellular homeostasis and antioxidant defense. In the excretory/secretory (E/S) products of Strongyloides ratti and Trichuris suis sequences for thioredoxin (Trx) and Trx-like protein (Trx-lp) were identified. To characterize the antioxidant Trx-lp and its interaction with the parasite’s mucosal habitat, S. ratti and T. suis Trx-lps were cloned and recombinantly expressed. The primary antioxidative activity was assured by reduction of insulin and IgM. Further analysis applying an in vitro mucosal 3D-cell culture model revealed that the secreted Trx-lps were able to bind to monocytic and intestinal epithelial cells and induce the time-dependent release of cytokines such as TNF-α, IL-22, and TSLP. In addition, the redox proteins also possessed chemotactic activity for monocytic THP-1 cells and fostered epithelial wound healing activity. These results confirm that the parasite-secreted Trx-lps are multifunctional proteins that can affect the host intestinal mucosa.